2014
DOI: 10.1124/dmd.113.054676
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Solute Carrier (SLC) Drug Uptake Transporter Loss in Human and Rat Cryopreserved Hepatocytes on Clearance Predictions

Abstract: Cryopreserved hepatocytes are often used as a convenient tool in studies of hepatic drug metabolism and disposition. In this study, the expression and activity of drug transporters in human and rat fresh and cryopreserved hepatocytes was investigated. In human cryopreserved hepatocytes, Western blot analysis indicated that protein expression of the drug uptake transporters [human Na + -taurocholate cotransporting polypeptide (NTCP), human organic anion transporting polypeptides (OATPs), human organic anion tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 54 publications
(74 reference statements)
3
26
0
Order By: Relevance
“…Lopinavir and rifampicin, however, gave less inhibition than predicted, and the inhibition by atazanavir was in the lower range of our predictions. This could indicate that the hepatic OATP1B1 expression/availability was lower in these hepatocyte batches than in the human liver tissue samples (Kimoto et al, 2012;Lundquist et al, 2014).…”
Section: Discussionmentioning
confidence: 77%
“…Lopinavir and rifampicin, however, gave less inhibition than predicted, and the inhibition by atazanavir was in the lower range of our predictions. This could indicate that the hepatic OATP1B1 expression/availability was lower in these hepatocyte batches than in the human liver tissue samples (Kimoto et al, 2012;Lundquist et al, 2014).…”
Section: Discussionmentioning
confidence: 77%
“…We recently showed that the apparent fexofenadine uptake in rat hepatocytes increased more than 4-fold when inhibiting P-gp during the uptake experiment (Lundquist et al, 2014b), supporting this hypothesis. As clearly shown in our present study, compensating for active efflux in the plated hepatocytes by calculating CL int,uptake,total (eq.…”
Section: Discussionsupporting
confidence: 61%
“…Short-term cultures of human cryopreserved hepatocytes should be investigated in future studies to help improve predictions of human biliary clearance. However, the pronounced down-regulation of OATP transporters that was recently demonstrated in human cryopreserved hepatocytes might present a limitation (Kimoto et al, 2012;Lundquist et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…These results should neither be affected by individual variation in transporter protein expression, nor by variation in the hepatocyte preparation, as absolute protein abundance measurements, as well as kinetic experiments, were performed for the same batch of human hepatocytes. Thus, even if transporter protein expression in cryopreserved hepatocytes would not represent transporter expression levels in freshly isolated or human liver samples, as indicated in studies by Kimoto et al (2012) and Lundquist et al (2014), the correlation between transporter protein expression and activity should not be affected, as protein abundances and transporter activities were determined for the same lot of hepatocytes in the present study. In contrast, given the substantial variation in reported transporter protein abundances between different hepatocyte lots or liver samples, it is crucial to characterize transporter expression in hepatocytes to compare with the respective activities.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in reported transporter activities and protein expression levels might be a result of substantial interindividual variation in transporter protein abundances observed in human liver samples (Nies et al, 2013;Vildhede et al, 2014). Furthermore, differences in hepatocyte isolation or transporter protein quantification procedures, as well as in the selection of reference peptides for QTAP analysis, were attributed to impact determined transporter protein abundances Lundquist et al, 2014). All studied statins are reported substrates of OATP1B1, and fluvastatin, rosuvastatin, pravastatin, and pitavastatin are substrates of OATP1B3 (Hirano et al, 2004;Neuvonen et al, 2006;Noe et al, 2007;Kalliokoski and Niemi, 2009).…”
Section: Discussionmentioning
confidence: 99%